OPTIMIZATION OF LATERITE ORE GRINDING PROCESS USING BALL MILL WITH RESPONSE SURFACE METHOD - Prameswara, Gyan; Tyassena, Flaviana Yohanala Prista; Amin, Idi; Hatimah, Husnul (Metalurgi, 2022)
Dependence and interaction between several operating conditions that affect the grinding process using a ball mill such as the number of balls, grinding duration, and rotational speed on particle size at 80% product mass (P80) and mineral liberation have been obtained in this study using a CCD (central composite design) of response surface method (RSM). The grinding process was carried out in a cylindrical ball mill with a diameter and length of 18.6 cm and 21.5 cm, respectively, as well as a steel ball with a diameter of 2.5 cm and a weight of 100 grams/ball. The optimum data for the grinding process was obtained with the smallest response value of P80. It was known that the number of balls and grinding duration have a significant effect on the reduction of the P80 value in the sample. The model that can describe the influence of process variables on the P80 value was obtained with good accuracy. The character of the mineral content of the sample was observed with the X-Ray Diffraction (XRD) pattern and the elemental concentration. Minerals that have a smaller hardness scale are easier to liberate and more exposed. The P80 value of the initial material was 1560.89 µm, while at the optimum condition the P80 grinding process was reduced to 513.29 µm.